PRODUCING GLOBAL MALAYSIAN SECONDARY STUDENTS THROUGH FOREIGN NOVELS: CHALLENGES - Yuet Zhou Tan; Azlina Abdul Aziz (University of Kuningan, 2019)
The study of literature provides a civilizing effect on a society anywhere around the world. Through these English kinds of literature, there are aspects of English culture encapsulated in it. This could potentially help students to develop as global citizens, which understand not only the feelings, settings, culture and even thoughts conveyed through the literature but being able to apply it to the real world, as a global citizen. If young students are not able to get such valuable exposure in schools, where are they supposed to receive such valuable input? Through this study, it is aimed to provide an overview of how foreign literature English novels chosen by the Ministry of Education has expanded the students' perspective as a global citizen. This paper aimed to reveal the challenges faced by teachers in using these texts in completing the objectives of producing students as global citizens. Thus, by applying Louise Rosenblatt Transactional Theory, it scaffolds this study to examine the challenges faced by English teachers in incorporating global citizenship values through the teaching of foreign novels in English. Data was collected via classroom observations, document analysis and interviews on both teachers and students. The data collected from the interviews, observations and item analysis were analyzed and results were conveyed in different themes, on the challenges faced by the respondents.Â